In Vivo Antioxidant Activity of Topical Cream of Cassia tora L. Leaves Extract. (9th May 2012) - Gupta, V.; Rathore, D. S.; Kansara, Niraj P.; Badiger, A. M.
Abstract : Objective . The aim of study was to determine the in vivo antioxidant activity of newly formulated O/W cream of methanolic extract of Cassia tora L. leaves. Methods . Oil in water (O/W) creams (0.05%, 0.1%, and 0.2%), cream base, methanolic extract of C. tora L. leaves (CTM), and standard (0.05% tretinoin cream) were screened for in vivo antioxidant activity. The ultraviolet- (UV-) B-induced rats were treated with different standard, O/W creams, cream base, and methanolic extract of Cassia tora L. leaves (CTM). The parameters like lipid peroxidation (LPO), reduced glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT) levels were assessed. Results . The result of acute dermal toxicity shows that the creams were safe up to 2000 mg/kg (topically). Exposure of ultraviolet light of medium wave (UV-B light) decreased the level of GSH, CAT, and SOD and increased the LPO level. Concluding Remarks . We conclude that topical O/W creams of C. tora L. prevent the oxidative stress induced in rats by exposure to UV-B light by virtue of its in vivo antioxidant property, and these findings help to understand the mechanism of the antipsoriatic activity of O/W creams of C. tora L. in UV-B-induced psoriasis in the rat.